Data and metadata reporting and presentation handbook - Ward, Denis (Organisation for Economic Co-operation and Development, 2007)
This publication contains guidelines and recommended best practice for the presentation of statistical data and metadata disseminated by national agencies and international organizations in various dissemination media. The handbook brings together in one publication relevant presentation guidelines embodied in existing international statistical standards where they exist. The handbook also presents for a standard set of terminologies and guidelines for the presentation of growth rates, indices and seasonally adjusted data developed by the OECD Short-term Economic Statistics Working Party.--Publisher's description.